Technical report: generating arabesque design of Masjid Nabawi sliding dome by a computer software / Tariq Ziad Abdul Razak, Tahmida Abdul Manaf and Nur Fatin Nabila Saupi - Abdul Razak, Tariq Ziad; Abdul Manaf, Tahmida; Saupi, Nur Fatin Nabila (2018)
Arabesque design is well known to be an epitome of Islamic art, and was developed as early as in the eighth century in middle East. Traditionally, arabesque design is drawn by hand where the eccentrical and aesthetical values of the design are highly regarded and appreciated. This research focus on how to generate an arabesque design by using mathematical software in order to gave a new way or perspective in producing an arabesque design. In this research the arabesque design of Masjid Nabawi sliding dome have been designed with the usage of Maple software. Mathematical transformations such as rotation, reflection and translation are used in order to complete the arabesque design.